2014
DOI: 10.1177/0003319714563138
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mortality Rates in Acute De Novo Versus Acute-on-Chronic Heart Failure

Abstract: Patients with ACHF had significantly higher long-term mortality rates than those with de novo acute heart failure (HF). Multidisciplinary HF disease management programs are highly needed for such high-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…The above-mentioned differences between the groups regarding the clinical characteristics observed in our AHF patients with worsening of CHF translated into a higher mortality rate, whereby the impact on 3-month mortality was more pronounced than the impact on hospital mortality. This is in line with two recent reports showing a strong association of the chronicity of HF with 6-month and 3-year mortality, but only a weak association with 1-month mortality 30 , 31 . In the present study, the strong association of worsening of CHF with 3-month mortality was weakened, but remained significant upon adjustment for comorbidities and established risk factors in HF 8 , 32 , 33 .…”
Section: Discussionsupporting
confidence: 93%
“…The above-mentioned differences between the groups regarding the clinical characteristics observed in our AHF patients with worsening of CHF translated into a higher mortality rate, whereby the impact on 3-month mortality was more pronounced than the impact on hospital mortality. This is in line with two recent reports showing a strong association of the chronicity of HF with 6-month and 3-year mortality, but only a weak association with 1-month mortality 30 , 31 . In the present study, the strong association of worsening of CHF with 3-month mortality was weakened, but remained significant upon adjustment for comorbidities and established risk factors in HF 8 , 32 , 33 .…”
Section: Discussionsupporting
confidence: 93%
“…than in de novo HF decompensation. 2,3 Furthermore, patients who receive a mechanical circulatory support system earlier in the course of disease or CHF achieve better outcomes than those with longstanding CHF before implantation. 5 Finally, in patients with a shorter duration of CHF, a lower rate of cardiovascular death and HF hospitalization was observed after CRT device implantation than in patients with longstanding symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic heart failure (CHF) is a clinical syndrome frequently accompanied by a high load of co-morbidities and characterized by poor outcomes, despite the provision of optimal medical patients. 2,3 Cardiac resynchronization therapy (CRT) initiated early after emerging HF symptoms improved clinical outcomes more than it did when applied later after the development of clinical symptoms. 4 In patients requiring mechanical circulatory support, outcome was better in acute or sub-acute HF than in patients with worsening of CHF and longstanding symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in accordance with the findings of the Finnish Acute Heart Failure Study (FINN-AKVA) with respect to a higher risk of mortality in the short-term and an equivalent risk on the long-term but stand apart from another report that found that the long –term survival is lower in ACS-AHF patients [ 22 , 23 ]. A few reports have highlighted the unfavorable long-term outcome of acute on chronic HF compared to de novo HF, including a report from our group [ 24 27 ]. Yet patients with ACS-AHF in our study, the majority of whom had de novo AHF, were not only at higher risk for hospital adverse cardiovascular outcomes but also had similar long-term survival rates compared to patients with NACS-AHF who predominantly presented with acute on chronic HF.…”
Section: Discussionmentioning
confidence: 99%